Model of method selection for managerial problem solving in an organization - Szarucki, Marek (Business, Management and Economics Engineering, 2013)
Managers at all levels must make various decisions while solving problems of their organizations. It is very important to select an appropriate method to solve a particular managerial problem. The purpose of this paper is to develop a model of method selection of managerial problem solving in an organization. In the beginning the theoretical background regarding managerial problems’ classification and methodological aspects of method selection for their solution are discussed. Further, the paper concentrates on the criteria of method evaluation and building a model helping at selecting the best method to solve the corresponding problem. It also makes an attempt to evaluate the perceived efficiency of the model as well as to provide potential dilemmas to its construction. Finally, some suggestions for future research are provided.